Does Leadership Style Improve Employee Performance? The Mediating Role of Incentives - Suparman, Dadang; Purnama, Reka Ardian (IJBLE Scientific Publications Community Inc., 2025)
From ancient times to the current era of digital disruption in the 5.0 society phase, the implementation of the right leadership style can improve employee performance, with effective work incentive policies playing a crucial role in strengthening it. The purpose of this study is to investigate whether leadership style can improve employee performance, by examining the mediating role of incentives. This research design uses a quantitative approach with a survey type, with the predictive power effect size relied on in the constructed research model. The research instrument was administered to 107 respondents as a research sample selected using a purposive sampling technique. Statistical analysis adapted the path analysis model by applying the SPSS PROCESS macro model to test the mediation effect. The research findings indicate that leadership style has a positive and significant direct and indirect effect on employee performance. Leadership style has a positive and significant effect on work incentives. Work incentives have a positive and significant mediation effect with moderate to strong predictive power. These findings can fill the existing gap and expand the literature in the field of human resource management and ideal behavior in business organizations. Leadership style can strengthen efforts to improve employee performance in business organizations, with work incentives acting as a crucial mediator that becomes a sensitive axis that decorates it appropriately can strengthen it.